1958
DOI: 10.1021/jf60087a011
|View full text |Cite
|
Sign up to set email alerts
|

Water Content of Meats, Determination of Water-Holding Capacity of Fresh Meats

Abstract: The only esters detected in the Fleischmann pre-ferment were those of acetic acid. The ethyl ester was presumably produced because of the high concentration of ethyl alcohol in the fermentation mixture. Wiseblatt (26) found only ethyl esters in bread crumb.The change in ethyl acetate concentration in the pre-ferment with time is shown in Figure 2. The ester reached its maximum concentration after 6 to 8 hours of fermentation and decreased to zero after 48 hours. The concentration of ethyl acetate in American D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
0
3

Year Published

1968
1968
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(120 citation statements)
references
References 11 publications
1
116
0
3
Order By: Relevance
“…Several studies have demonstrated that as muscle pH increases there is an accompanying increase in waterbinding capacity of the muscle proteins (Wierbicki and Deatherage, 1958). WHC at 24 h post mortem of meat from lambs transported for 30 min was higher than those from lambs transported for 5 h. Although pressure loss was not significantly affected by the factors studied, cooking loss was lower in lambs transported for 30 min than in those transported for 5 h. Decreased cooking loss is a reflection of the increased WHC associated with meat of high ultimate pH (Bouton et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that as muscle pH increases there is an accompanying increase in waterbinding capacity of the muscle proteins (Wierbicki and Deatherage, 1958). WHC at 24 h post mortem of meat from lambs transported for 30 min was higher than those from lambs transported for 5 h. Although pressure loss was not significantly affected by the factors studied, cooking loss was lower in lambs transported for 30 min than in those transported for 5 h. Decreased cooking loss is a reflection of the increased WHC associated with meat of high ultimate pH (Bouton et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…The measurements were performed on a freshly cut surface of 2.5 cm thick LT (12th-13th ribs) after allowing the muscle surface to bloom in the chiller for 45 min. Water-holding capacity (WHC) was determined according to Wierbicki and Deatherage (1958), where a 0.5 g sample of muscle tissue was placed on filter paper and pressed at 500 psi min −1 between two plexiglass plates. The results were expressed as the percentage of free water.…”
Section: Sampling Procedures and Instrumental Analysesmentioning
confidence: 99%
“…Water-holding capacity (WHC) was estimated by determining expressible juice using a modification of the filter paper press method described by Wierbicki and Deatherage (1958). Briefly, a raw meat sample weighing about 1000 mg was placed between 18 pieces of 11-cm diameter filter paper and pressed at 35 kg for 5 min.…”
Section: Water-holding Capacity Measurementmentioning
confidence: 99%